1979
DOI: 10.7901/2169-3358-1979-1-709
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Distribution and Weathering Characteristics at a Tropical Oil Spill Site

Abstract: A study was performed on the state of an oil spill site on the southwest coast of Puerto Rico. The location of the study was Bahia Sucia, the site of the Zoe Colocotroni spill of 17 March, 1973. Particular attention was given to the weathering characteristics of the stranded oil remaining at the sites and to the presence of biogenic hydrocarbons in the sediments. High resolution gas chromatography of the aliphatic and aromatic fractions of the sediment hydrocarbons was used to distinguish the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The anaerobic conditions and low redox potential values found in mangrove sediments are known to be unfavorable for the biodegradation of hydrocarbons [58], and substantial concentrations of hydrocarbons remain in mangrove sediments 10 to 30 years after spills [59,60]. Three years after the Zoe Colocotronis spill in Puerto Rico, soil samples from the mangrove community had up to 80,000 ppm extractable hydrocarbons [61]. Mangroves can translocate aromatic hydrocarbons into their tissues [46], and the toxic components of retained oil continue to cause sublethal effects, including reduced productivity, lower rates of litter production, and lower seedling survival [62].…”
Section: Status Of Knowledge About Chemical Stressors In Tropical Marmentioning
confidence: 99%
“…The anaerobic conditions and low redox potential values found in mangrove sediments are known to be unfavorable for the biodegradation of hydrocarbons [58], and substantial concentrations of hydrocarbons remain in mangrove sediments 10 to 30 years after spills [59,60]. Three years after the Zoe Colocotronis spill in Puerto Rico, soil samples from the mangrove community had up to 80,000 ppm extractable hydrocarbons [61]. Mangroves can translocate aromatic hydrocarbons into their tissues [46], and the toxic components of retained oil continue to cause sublethal effects, including reduced productivity, lower rates of litter production, and lower seedling survival [62].…”
Section: Status Of Knowledge About Chemical Stressors In Tropical Marmentioning
confidence: 99%
“…There are three major hydrocarbon types: (1) petrogenic hydrocarbons related to crude oil and its refined products; (2) biogenic hydrocarbons generated by biologic or diagenetic processes; and (3) pyrogenic hydrocarbons generated by high temperature processes [4], including forest fires and fossil-fuel combustion. For example, Page et al [5] documented multiple sources of petroleum and biogenic hydrocarbons in the Amoco Cadiz impact zone; mangrove leaf waxes [6] were shown to be a major source of biogenic hydrocarbons in a tropical spill site; and Page et al [2] identified numerous hydrocarbon sources in Prince William Sound subtidal sediments, including pyrogenic polycyclic aromatic hydrocarbons (PAHs) primarily associated with sites of past or current human use (see also Bence et al [7]), weathered Exxon Valdez oil residues from subtidal areas close to some heavily oiled shorelines, and a regional background of oil-seepderived petroleum distributed throughout the seafloor sediments in the sound. The identification of this regional petroleum background was subsequently confirmed by benthic sediment studies conducted by others in 1993 [8].…”
Section: Review Of Hydrocarbon Sources In Prince William Sound and Thmentioning
confidence: 99%
“…Nadeau and Bergquist (1977); Page et al (1979) Getter et al (1981) Lasday et al (1981 Reports in the literature of oil pollution damage to mangroves include the following, given in Table 3. Large trees not defoliated at this stage.…”
Section: 1 Information Summarymentioning
confidence: 99%